Developing genetic learning module based on blue eyes phenomenon in Buton Island, Southeast Sulawesi - Slamet, Agus; Taharu, Fahmil Ikhsan; Hudha, Atok Miftachul (University of Muhammadiyah Malang, 2019)
The existence of learning resources based on local phenomena is presumed to be able to optimize genetic learning processes. The purposes of this study were (1) to produce module based on the blue eyes phenomenon occurred in Buton Island for genetic material in senior high school and (2) to find the quality of the module produced. This study used research and development (R & D) based on Borg & Gall model which was limited to seventh step. The research involved three validators, six students in initial field-testing step, and 70 students in main field testing. The data collection technique used was questionnaire. The data obtained were calculated as percentages of module quality. The results of the material validation, media validation, and practitioners were 96.52% (very valid); 82.40% (very valid); and 83.75% (very valid), respectively. In addition, the student responses to the module was 22.13% (good). In conclusion, this module can be used as a learning resource for senior high school students in genetic learning.